(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Perets O. B. The content and structure of readiness of the future teacher of natural and mathematics disciplines to the pedagogical planning by means of information technologies. In the article the problem of readiness of the future teacher of natural and mathematical disciplines to the pedagogical planning by means of information technologies has been analyzed. The content of the above mentioned readiness of the future teacher of natural and mathematical disciplines has been defined and scientifically grounded.